Landscape architecture : a manual of site planning and design - Simonds, John Ormsbee (New York : McGraw Hill Education, 1983)
This book has been written in response to the need for a book outlining the site-planning process in clear, simple, and practical terms. It introduces us to an understanding of nature as the background and base for all human activities.
1. Fundamentals -- 2. Land -- 3. Water -- 4. Plants -- 5. Climate -- 6. Site -- 7. Spaces -- 8. Visible landscape -- 9. Circulation -- 10. Structures -- 11. Habitations -- 12. Community -- 13. The city -- 14. Region -- 15. Environment.
Includes bibliographical references and index.
Keywords: LANDSCAPE ARCHITECTURE